Healthcare Access of Autistic Language Minorities: The Case of English Official Language Minorities in Quebec, Canada - Amantayev, Nariman; Rao, Sabrina; Nadig, Aparna (Minorités linguistiques et société, 2025)
Abstract English and French are both official languages in Canada. Whereas official language minorities (English speakers in Quebec, French speakers in the rest of Canada) face healthcare barriers and poor health outcomes, autistic individuals and their families also struggle with accessing healthcare. We examined healthcare access at the intersection of these groups: the autistic community, including English minority-language speakers from Quebec, French majority-language speakers from Quebec, and English majority-language speakers from elsewhere in Canada (n = 165). Linguistic minorities reported poorer access to publicly-funded services and lower satisfaction that their language needs were being met than did linguistic majorities. Foreign-born English speakers also experienced poorer access than their Canadian-born counterparts. These preliminary findings suggest that autistic language minorities face known barriers to accessing healthcare, potentially at a higher rate than that experienced by language minorities in general. Résumé L’anglais et le français sont les langues officielles du Canada. Les minorités de langue officielle (anglophones au Québec, francophones hors Québec) font face à des obstacles en matière de santé, tout comme les personnes autistes et leurs familles. Nous avons examiné l’accès aux services de santé à l’intersection de ces groupes : la communauté autiste, incluant des anglophones (minoritaires) et francophones (majoritaires) du Québec, ainsi que des anglophones (majoritaires) du reste du Canada (n = 165). Les minorités linguistiques déclarent un accès plus difficile aux services de santé publics et une moindre satisfaction quant à la prise en compte de leurs besoins linguistiques, comparativement aux majorités linguistiques. Les anglophones nés à l’étranger rapportent également un accès plus difficile que leurs pairs nés au Canada. Ces résultats préliminaires suggèrent que les minorités linguistiques autistes font face à des obstacles connus en matière d’accès aux soins, possiblement à un degré plus élevé.

Healthcare Service Utilization and Perceived Gaps: The Experience of French-Speaking 2S/LGBTQI+ People in Manitoba - de Moissac, Danielle; Prada, Kevin; Gueye, Ndeye Rokhaya; Avanthay-Strus, Jacqueline; Hardy, Stephan (Healthcare Policy, 2024)
Ethnolinguistically diverse 2S/LGBTQI+ (two-spirit, lesbian, gay, bisexual, transgender, queer and intersex) populations have unique healthcare needs and experience health inequities compared to their cisgender or heterosexual peers. This community-based participatory study sought to describe the profile and healthcare needs and experiences of official language minority French-speaking 2S/LGBTQI+ adults in Manitoba. Participants (N = 80) reported that gender and sexual identity were often concealed from service providers; many respondents faced discrimination based on their ethnolinguistic and sexual identities. Service gaps are identified pertaining to mental and sexual health; locating 2S/LGBTQI+-friendly, patient-centred care in French is difficult. Policy and practice should address systemic inequity and discrimination experienced by this equity-seeking population.

Language barriers and healthcare access: a qualitative study in the Volta Region of Ghana - Glover-Meni, Nathaniel; Nyarko, Joy Ato; Agbezorlie, Peter K.; Agyei, Dominic Dankwah (Journal of Communication in Healthcare, 2024)
Background The study explores the language barriers between two language minority populations and healthcare professionals in the Volta Region of Ghana. Methods An interpretive description with a qualitative approach to data collection and analysis was used. This study was carried out in the Tafi-Atome and Avatime-Vane communities, the Hohoe Municipal Hospital and the Margaret Marquart Catholic Hospital in the Kpando Municipality. In all, 46 respondents comprising 19 purposively sampled community members (patients) from the two selected communities and 27 conveniently sampled healthcare professionals from the two health facilities were interviewed. The face-to-face in-depth interviews were audio-recorded, transcribed and thematically analysed. Results The study revealed a barrier in language use between healthcare professionals and patients from the two language minority communities. While healthcare professionals preferred to use English, Akan and Ewe, the patients, on the other hand, preferred their native languages, which are Sideme and Tegbor. The services of unqualified interpreters were utilised by both healthcare professionals and patients. Study participants were aware of these challenges, which prevented the patients from receiving optimum healthcare services, and the healthcare workers from delivering client-centred healthcare services. Conclusions The presence of communication challenges emanating from language barriers between healthcare professionals and patients should be considered as a key hindrance to the attainment of the Sustainable Development Goal Three (SDG3), which aims to promote health and well-being at all ages. Therefore, stakeholders in the healthcare delivery system in Ghana need to prioritize stronger communication and translation practices and policies.

Final Report – Improving the Francophone Experience in Healthcare - Réseau du mieux-être francophone du Nord de l'Ontario (2021)

Rapport final – Amélioration de l’expérience des francophones dans les soins de santé - Réseau du mieux-être francophone du Nord de l'Ontario (2021)

Language related difficulties experienced by caregivers of English-speaking seniors in Quebec - Sanderson, Duncan (SAGE Open, 2020)
Little research has examined communication problems between speakers of official minority languages (patients or caregivers) and health care providers. The objective of this research was to identify the types of issues experienced by English-speaking caregivers of seniors in Quebec, as they interact with French-speaking health care providers. The majority of the caregivers interviewed indicated that they were satisfied with physicians’ interaction with the seniors they cared for. However, problems included health care providers who do not or who refuse to speak English, hospice personnel with insufficient English, anxiety about speaking to personnel in French, traveling to receive services in English, acting as an informal interpreter, receiving written documents in French, scheduling appointments through French-only phone systems or receptionists, and discrimination. The main finding is that in Quebec, language asymmetry might create additional stresses for an English-speaking caregiver, who is already likely to be stressed because of their caregiver role.

Access to healthcare services and confidence in healthcare professionals’ management of malaria: the views of Francophone sub-Saharan African Immigrants living in western Canada - Vincent, Rémi; Coulibaly, Kongnon Sangué; Ahmed, Ali; Ahmed, Youssef; Hanna, Taylor A.; Ravi, Srilata; Hawkes, Michael T.; Gnidehou, Sedami (BMC Public Health, 2023)
Abstract Background There is a paucity of knowledge about the healthcare attitudes and practices of French-speaking immigrants originating from Sub-Saharan Africa (FISSA) living in minority settings. The purpose of this study was to characterize FISSA healthcare experiences and confidence in the malaria-related knowledge of health professionals in Edmonton. Methods A structured survey was used to examine a cohort of 382 FISSA (48% female; 52% male) living in Edmonton. FISSA general healthcare attitudes, experiences and satisfaction with the Canadian healthcare system were studied. Healthcare Competency Perception (HCP) was characterized by using an index score. Statistical analyses were performed to evaluate the impact of healthcare experiences and other outcomes. Results Intriguingly, while only 42% of FISSA had a French-speaking family physician, 83% (197/238) of those who had received health care services in Alberta found that access to medical treatment was easy, and 77% (188/243) were satisfied with received care. Although 70% (171/243) of FISSA did not receive services in French, 82% (199/243) surprisingly reported having good levels of comprehension during their visits. Satisfaction with care was associated with having a family physician (p = 0.018) and having health insurance (p= 0.041). Nevertheless, confidence in the healthcare system’s ability to treat malaria effectively was significantly lower, with only 39% (148/382) receiving a positive score on the HCP index. Conclusion This study provides an important insight into FISSA experience with and perception of the Alberta’s healthcare system.